Peningkatan Hasil Belajar Pendidikan Agama Islam Pokok Bahasan Ketentuan Pernikahan dalam Islam Melalui Model Pembelajaran Kooperatif Typestad (Student Teams Achievement Division) pada Siswa Kelas XI TKJ A SMK Negri 3 Kaur - Lipa Andisi (GHAITSA : Islamic Education Journal, 2025)
This research was conducted in class XI TKJ A SMKN 3 Kaur in the odd semester of the 2024/2025 academic year. This research was set in 2 cycles, in the subject of Islamic Religious Education. Acting as a model teacher is the researcher himself, collaborating with teachers at the school who act as observers. The object of the research was 17 students of class XI TKJ A. This research is included in the type of Classroom Action Research. The typical characteristic of classroom action research is the existence of certain actions to improve the teaching and learning process in the classroom. From the research data, it is known that the implementation of the STAD type cooperative learning model in Islamic Religious Education learning in class XI TKJ A at SMKN 3 Kaur can increase student group activity and teacher activity. This can be seen from the achievement of the average value in each cycle. Student group activity increased from cycle I with an average activity value of 2.38 in the less good category to 3.5 in the good category in cycle II. Teacher activity also increased better than cycle I with an average activity value of 2.6 in the fairly good category to 3.76 in the good category in cycle II. In addition, the implementation of the STAD type cooperative learning model can improve Islamic Religious Education learning outcomes in class XI TKJ A students at SMKN 3 Kaur. The average value in cycle I was 68.82, and increased by 14.75% with an average value in cycle II of 79.00 in cycle II. In addition, the number of students who had completed learning increased to 16 students or 94.11%.